2020
DOI: 10.1186/s43556-020-00006-z
|View full text |Cite
|
Sign up to set email alerts
|

cGAS/STING: novel perspectives of the classic pathway

Abstract: Cyclic GMP-AMP (cGAMP) synthase (cGAS) is a cytosolic DNA sensor and innate immune response initiator. Binding with exogenous or endogenous nucleic acids, cGAS activates its downstream adaptor, stimulator of interferon genes (STING). STING then triggers protective immune to enable the elimination of the pathogens and the clearance of cancerous cells. Apparently, aberrantly activated by self-DNA, cGAS/STING pathway is threatening to cause autoimmune and inflammatory diseases. The effects of cGAS/STING in defens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 163 publications
(210 reference statements)
1
16
0
Order By: Relevance
“…Notably, we found that four out of the six tumor types analyzed here have decreased cytosolic DNA sensing pathway signaling in p16-low vs. p16-high tumors ( Supplementary Figure 4B ); however, no correlation was found between CDKN2A and LMNB1 mRNA expression ( Figure 4C ), suggesting that additional mechanisms are at play in tumors with low p16 expression. It is important to note that besides loss of nuclear integrity, there are other phenomena (mitochondrial DNA leakage, upregulation of LINE-1, or increased expression of the endonuclease MUS81) that may contribute to an impaired cytosolic DNA sensing pathway (reviewed in [ 87 ]). Loss of CDKN2A is often due to deletion or hypermethylation of the locus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that four out of the six tumor types analyzed here have decreased cytosolic DNA sensing pathway signaling in p16-low vs. p16-high tumors ( Supplementary Figure 4B ); however, no correlation was found between CDKN2A and LMNB1 mRNA expression ( Figure 4C ), suggesting that additional mechanisms are at play in tumors with low p16 expression. It is important to note that besides loss of nuclear integrity, there are other phenomena (mitochondrial DNA leakage, upregulation of LINE-1, or increased expression of the endonuclease MUS81) that may contribute to an impaired cytosolic DNA sensing pathway (reviewed in [ 87 ]). Loss of CDKN2A is often due to deletion or hypermethylation of the locus [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It plays a central role in releasing mitochondrial ROS (mROS) from the intermembrane space [ 67 ], and VDAC oligomers interact with mtDNA to release it into the cytosol [ 68 ]. mROS release in the cytosol can cause nuclear DNA damage, triggering pro-apoptotic signaling [ 60 ], whereas cytosolic presence of mtDNA can activate the cGAS/STING signaling leading to inflammatory cell death [ 69 ].…”
Section: The Role Of Mitochondria In Intrinsic Apoptosis and Inflammatory Cell Deathmentioning
confidence: 99%
“…The cGAS/STING pathway also plays a role in cell senescence. Accumulated oxidative damage to mitochondrial membrane proteins and lipids in senescent cells increases membrane permeability, leading to membrane break-up [ 69 , 71 ]. Here, the binding of cGAS to mtDNA activates the expression of NF-κB and triggers secretion of senescence-associated secretory phenotype (SASP) factors, including Interleukine-6 (IL-6), C-X-C motif chemokine 10 (CXCL10), TNF-α, and several other chemokines.…”
Section: The Role Of Mitochondria In Intrinsic Apoptosis and Inflammatory Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Notably, while self-DNA sensing by cGAS is implicated in the response to cellular stress and tissue damage, overactive cGAS-STING signaling pathway caused by self-DNA leads to inflammatory and autoimmune disease. 125 Interestingly, membrane, cytosolic and nuclear localization of cGAS was all detected. Membrane localization of cGAS minimizes its activation by self-DNA.…”
Section: Perspectivesmentioning
confidence: 97%